A Review of the Applications of Marine CSEM Method in Offshore Resource Exploration and Environmental Studies - Ofubu, Ebimobowei Emmanuel; Folorunso, Adetayo Femi; Chukwusa, Francis Onyemaechi (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
A review of the applications of marine Controlled-Source Electromagnetic (mCSEM) method in offshore resource explorations and environmental studies is undertaken in this paper. Initially revisited for offshore hydrocarbon exploration, CSEM has expanded its utility beyond this to other application in the offshore industry such as production monitoring, environmental studies, and even sub-seafloor groundwater mapping, due to its ability to isolate high resistive layer below the mudline. This study looks into the fundamental principles of CSEM, including electromagnetic induction and wave propagation, and delves into its instrumentation, survey design, and data interpretation processes. Key concepts such as shared earth modeling, seabed isotropy, resistivity variations, and attribute analyses are examined to enhance the understanding of CSEM's effectiveness in mapping subsurface conductivity. Significant advancements in CSEM technology and methodologies have addressed challenges associated with marine environments, making it a reliable and cost-effective tool for offshore exploration. The study highlights the potential impact of CSEM on various industries, including energy and mining, and underscores its importance in the ongoing evolution of geophysical exploration techniques.